2012
DOI: 10.1002/dta.1336
|View full text |Cite
|
Sign up to set email alerts
|

The detection of the urinary metabolites of 1‐[(5‐fluoropentyl)‐1H‐indol‐3‐yl]‐(2‐iodophenyl)methanone (AM‐694), a high affinity cannabimimetic, by gas chromatography – mass spectrometry

Abstract: AM-694 (1-[(5-fluoropentyl)-1H-indol-3-yl]-(2-iodophenyl)methanone), a synthetic indole-based cannabimimetic, was first reported to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) via the Early Warning System (EWS) by Irish authorities in 2010. Using gas chromatography-mass spectrometry (GC-MS), we have identified six AM-694 metabolites in post-ingestion samples. The metabolites were tentatively identified as products of (1) hydrolytic defluorination, (2) carboxylation, (3) monohydroxylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 12 publications
5
35
0
Order By: Relevance
“…In this paper we describe for the first time in Italy the report of an intoxication where the SC AM-694 (see Figure 1) and its main metabolites, the hydrolytically defluorinated metabolite, M1 and the carboxylated metabolite, M2, [25] (see Figure 2) were identified in biological fluids (urine) by LC-MS/MS. AM-694 or 1-(5-fluoropentyl)-3-(2-iodobenzoyl)indole is an aminoalkylindole.…”
Section: Page 6 Of 28mentioning
confidence: 97%
“…In this paper we describe for the first time in Italy the report of an intoxication where the SC AM-694 (see Figure 1) and its main metabolites, the hydrolytically defluorinated metabolite, M1 and the carboxylated metabolite, M2, [25] (see Figure 2) were identified in biological fluids (urine) by LC-MS/MS. AM-694 or 1-(5-fluoropentyl)-3-(2-iodobenzoyl)indole is an aminoalkylindole.…”
Section: Page 6 Of 28mentioning
confidence: 97%
“…A volunteer study investigating the metabolites of AB-001 found that they were detectable for up to 160 hours following oral administration [35], while metabolites of AM-694 were detected up to 117 hours post oral ingestion [23]. Analysis of thirty-four urine samples collected from patients admitted with suspected drug intoxication revealed metabolites of JWH-203 (n = 28), JWH-251 (n = 8), JWH-250 (11 of the JWH-203 samples) and JWH-018 (1 of the JWH-203 samples) [36].…”
Section: Pharmacokineticsmentioning
confidence: 98%
“…Whilst the pharmacokinetics of these substances remains largely unknown, there are some data available from a combination of clinical cases, studies and self-experiments [1,16,[21][22][23] (Gardin 2009). Because of the wide chemical diversity of the SCRAs it is not possible to extrapolate pharmacological properties between, and potentially within, different SCRA classes.…”
Section: Pharmacokineticsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, in hair (and in keratinized matrices in general) parent, un-metabolized drugs accumulate prevalently, in comparison with the corresponding metabolites [13]. Conversely, studies performed both in vivo and in vitro on some of the synthetic cannabinoids showed that they are extensively metabolized, and in many cases no parent compound is detectable in urine [14][15][16][17][18]. Thus, whereas the determination of synthetic cannabinoids in urine and blood will therefore be faced with the issue of identifying several metabolites often not well known, hair analysis can be focussed directly on the parent drug.…”
Section: Introductionmentioning
confidence: 98%